STUDENTS PERCEPTION OF LIMITED FACE-TO-FACE LEARNING MANAGEMENT DURING PANDEMIC IN ISLAMIC EDUCATION CLASS - Hega Nurazizah (Institut Ummul Quro Al-Islami Bogor, 2023)
This study aims to determine students' perceptions of limited face-to-face learning during the COVID-19 pandemic at SMAN 1 Singaparna in the 2021/2022 academic year. The research method used is a qualitative method with a descriptive qualitative approach with data collection techniques in the form of an open questionnaire to class XI MIPA 4 AND XI MIPA 5, especially in the subject of Islamic education SMAN 1 Singaparna. The results showed that the students towards this limited face-to-face learning were very enthusiastic. With limited face-to-face learning, students can return to school and interact with teachers and their peers, can directly receive lessons from the teacher, and can discuss related lessons learned. This makes the learning process more enjoyable. The learning delivered by the teacher is easier to understand because the teacher explains directly not only giving assignments so that this limited face-to-face learning is the right solution to the problems faced by students during distance learning